2009
DOI: 10.1103/physrevlett.102.073001
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Retrieval of Target Structures and Laser Parameters of Few-Cycle Pulses from Photoelectron Momentum Spectra

Abstract: We illustrate a new method of analyzing three-dimensional momentum images of high-energy photoelectrons generated by intense phase-stabilized few-cycle laser pulses. Using photoelectron momentum spectra that were obtained by velocity-map imaging of above-threshold ionization of xenon and argon targets, we show that the absolute carrier-envelope phase, the laser peak intensity, and pulse duration can be accurately determined simultaneously (with an error of a few percent). We also show that the target structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
56
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 24 publications
4
56
0
Order By: Relevance
“…24,25 A peak intensity in the focus of 1.3(AE0.3) Â 10 14 W cm À2 was determined from the cutoff in electron spectra recorded for Xe 23,26 under the same experimental conditions as for the molecular experiments. Ions or electrons that were generated at the laser focus in the VMI spectrometer were projected onto an MCP/phosphor screen assembly using a static electric field.…”
Section: Resultsmentioning
confidence: 99%
“…24,25 A peak intensity in the focus of 1.3(AE0.3) Â 10 14 W cm À2 was determined from the cutoff in electron spectra recorded for Xe 23,26 under the same experimental conditions as for the molecular experiments. Ions or electrons that were generated at the laser focus in the VMI spectrometer were projected onto an MCP/phosphor screen assembly using a static electric field.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been reported that the stereo-ATI signal alone is sufficient to estimate both the CEP and the duration of the pulses at the same time with the help of quantitative rescattering theory [53][54][55] or calibration with external SPIDER measurements 56 . However, the method is insensitive to the structures below 30% of the peak intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus often only HATI spectrum is used to retrieve the CEP since it offers greater contrast in its left-right asymmetry [14] instead of the low-energy ATI electrons [15]. Using the cutoff position of the HATI electrons, the CEP values of few-cycle pulses have been retrieved by comparing theory with experiments [13,14,16]. However such a method assumes that the laser duration and intensity are known accurately.…”
mentioning
confidence: 99%
“…In the classical recattering model, the electron is tun- nelling ionized near the peak of the laser field and returns to the ion after three quarters of an optical cycle when the electric field is about zero and the vector potential reaches its maximum A 0 [13,28]. Only considering the outermost portion of the wave packet, its strength is related to the electric field at the tunneling ionization time and its momentum is related to A 0 at the returning time.…”
mentioning
confidence: 99%
See 1 more Smart Citation